Harmonic and Intermodulation Performance of Nonlinear Electronic Circuits - Muhammad Taher Abuelma'atti (Active and Passive Electronic Components, 1998)
A unified technique for mathematical modelling of the input output characteristics of nonlinear electronic circuits is presented. This technique can be easily implemented using simple hand computations without recourse to standard curve-fitting techniques, which invariably requires extensive computing facilities and well-developed software. The mathematical model, basically a sine-series function, can easily yield closed-form series expressions for the amplitudes of the output components resulting from a multisinusoidal input signal to nonlinear electronic circuits. The technique is very helpful in analysing nonlinear electronic circuits under different scenarios of input signals.